D8/17 Monoclonal Antibody: An Unclear Neuropsychiatric Marker - Astrid Morer; Odette Viñas; Luisa Lázaro; Jordi Bosch; Josep Toro; Josefina Castro (Behavioural Neurology)
Objective: It has been hypothesized that monoclonal antibody D8/17 identifies a B lymphocyte antigen with expanded expression in patients with rheumatic fever, childhood onset obsessive-compulsive disorder (OCD), Tourette syndrome (TS) or prepubertal anorexia nervosa (AN). Our purpose was to replicate these studies in a Spanish population and to determine whether D8/17 identifies a subgroup of these patients, focusing especially on OCD subjects.